The Degradation of The Kaili Edo Dialect Among the Younger Generation in Sibalaya Village, Tanambulava District - Mu’jizat, Mu’jizat (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
This study aims to explore and analyze the various factors contributing to the decline in the use of the Kaili language among the younger generation in Sibalaya Village, Tanambulava District. The focus is on its diminishing role as both a daily social language and a medium for conveying the cultural values of the Kaili tribe. A qualitative approach is employed, as the data collected consists primarily of oral and written narratives. Data collection methods include observation, in-depth interviews, and document analysis, with the findings analyzed using qualitative descriptive techniques. The results indicate that several factors contribute to the decline of the Kaili language in Sibalaya Village, particularly among the younger generation. These include social changes and the influence of modernization. Nonetheless, the Regional Government of Sigi Regency is actively working to address this issue by incorporating the Kaili language into the curriculum of all schools in the regency.